Modulation of the adsorption chemistry of a precursor in atomic layer deposition to enhance the growth per cycle of a TiO2 thin film. Issue 4 (20th October 2020) - Cho, Yeonchoo; Kim, Sang Hyeon; Kim, Byung Seok; Kim, Youngjin; Jeon, Woojin
Abstract : This study investigates the chemical reaction mechanism of the ALD to obtain a designated growth behaviour in theoretical and experimental way, hence, provides significant implications for understanding the ALD mechanism based on the DFT calculation. Abstract : Atomic layer deposition (ALD) has scarcely been utilized in large-scale manufacturing and industrial processes due to its low productivity, even though it possesses several advantages for improving the device performance. The major cause of its low productivity is the slow growth rate, which is determined by the amount of chemisorbed precursor. The slow growth rate of ALD has become even more critical due to the introduction of heteroleptic-based precursors for achieving a higher thermal stability. In this study, we investigated the theoretical and experimental chemisorption characteristics of the Ti(CpMe5 )(OMe)3 precursor during the ALD of TiO2 . By density functional theory calculations, the relationship between the steric hindrance effect and the chemistry of a chemisorbed precursor was revealed. Based on the calculation result, a way for improving the growth per cycle by 50% was proposed and demonstrated, successfully.